The co-expression of the depolarizing and hyperpolarizing mechanosensitive ion channels in mammalian retinal neurons - Pang, Vivian Y.; Yang, Zhuo; Wu, Samuel M.; Pang, Ji-Jie (Frontiers in Medicine, 2024)
Introduction: The elevation of the intraocular and extraocular pressures is associated with various visual conditions, including glaucoma and traumatic retinal injury. The retina expresses mechanosensitive channels (MSCs), but the role of MSCs in retinal physiology and pathologies has been unclear. Methods: Using immunocytochemistry, confocal microscopy, and patch clamp recording techniques, we studied the co-expression of K + -permeable (K-MSCs) TRAAK and big potassium channel BK with the epithelial sodium channel ENaC and transient receptor potential channel vanilloid TPRV4 and TRPV2 favorably permeable to Ca 2+ than Na + (together named N-MSCs), and TRPV4 activity in the mouse retina. Results: TRAAK immunoreactivity (IR) was mainly located in Müller cells. Photoreceptor outer segments (OSs) expressed BK and ENaCalpha intensively and TRAAK, TRPV2, and TRPV4 weakly. Somas and axons of retinal ganglion cells (RGCs) retrograde-identified clearly expressed ENaCalpha, TRPV4, and TRPV2 but lacked TRAAK and BK. Rod bipolar cells (RBCs) showed TRPV4-IR in somas and BK-IR in axonal globules. Horizontal cells were BK-negative, and some cone BCs lacked TRPV4-IR. TRPV4 agonist depolarized RGCs, enhanced spontaneous spikes and excitatory postsynaptic currents, reduced the visual signal reliability (VSR=1-noise/signal) by ~50%, and resulted in ATP crisis, which could inactivate voltage-gated sodium channels in RGCs. Conclusions: Individual neurons co-express hyperpolarizing K-MSCs with depolarizing N-MSCs to counterbalance the pressure-induced excitation, and the level of K-MSCs relative to N-MSCs (RK/N ratio) is balanced in the outer retina but low in RGCs, bringing out novel determinants for the pressure vulnerability of retinal neurons and new targets for clinical interventions.